UPAYA GURU BIMBINGAN DAN KONSELING UNTUK MELAKSANAKAN PROGRAM BIMBINGAN KARIR DI SMA N 14 PADANG - Wulandari, Kiki; Kasih, Fitria; Yusnetti, Yusnetti (Bimbingan dan Konseling, 2013)
Based on phenomena that occur in field where visible presence errors, omissions and inaccuracies in making decisions about further education learners who will have lived a bleak outlook in determining the direction of a career choice . Such problems often faced by learners , especially to determine type of education which one should take, and how prospects for employment or career after graduating , and how steps that must taken to prepare themselves in entering employment or career in the future . This research conducted using qualitative methods and descriptive approach that intends to get an overview of career guidance program in Public of Senior High School 14 Padang . Key informants in this study the counselor. The counselor totaling three person . The results of this study were ( 1 ) study feasibility of the implementation career guidance that has been done by the counselor in Public of Senior High School 14 Padang had adapted to talents and interests of learners so learners can determine enthuses career ( 2 ) career guidance programming pursued by counselor adapted to needs of learners . Having mind need or needs assessment learners counselor working to develop a career guidance program will be given to students.